Anesthetic considerations in scoliosis patient with dopa-responsive dystonia or Segawa's syndrome: Two case reports and a review of the literature. (6th February 2017) - Hasan, M Shahnaz; Leong, Kok Weng; Chan, Chris Yin Wei; Kwan, Mun Keong
Segawa's syndrome or dopa-responsive dystonia is a rare hereditary disorder characterized by progressive dystonia of childhood onset, diurnal fluctuation of symptoms and complete or near complete alleviation of symptoms with administration of low-dose oral levodopa. From our literature search in PubMed, we found only three related publications: two on anesthesia for cesarean section and one on anesthesia for electroconvulsive therapy. We report our experience in providing anesthesia for corrective scoliosis surgery in two biological sisters with Segawa's syndrome. A review of the literature is also included.